Smart Hanger: Indoor T-Shirt Dryer - ZAHAR, MOHD MUZAFFAR; Zainuddin, Mohamad Ikram Danial; Abd Raof, Nor Adawiyah; Ismady, Nurul Syafiqah (Multidisciplinary Applied Research and Innovation, 2020)
The uncertain weather problem had been causing people to have a hard time doing their laundries as daily chores. A lot of people had been going to the dobby because of this unsettled weather with rain and sunshine coming after one another. However, to do this for a long time can cost a lot, energy and money. With the right innovation, it can make living easier for people. The technology needs to be simple to be used, portable and includes fast drying. A technology like a hanger that has cooling, drying and heating settings could easily help the problem of clothes drying as the weather is not consistent and sometimes not even the weather forecast could predict precise upcoming weather. Hanging clothes indoor without the proper techniques can cause unpleasant smell for the clothing since there are no sunlight or heating elements. And also, the trapped air inside the house helps with the bad smell of clothing. Hence, the use of smart hanger is the right way to hang clothes indoor.